Cryptotanshinone inhibits ovarian tumor growth and metastasis by degrading c-Myc and attenuating the FAK signaling pathway - Guo, Huijun; Zhang, Wenjing; Wang, Jiaxing; Zhao, Guannan; Wang, Yaohong; Zhu, Bing-Mei; Dong, Peixin; Watari, Hidemichi; Wang, Baojin; Li, Wei; Tigyi, Gabor; Yue, Junming (Frontiers in Cell and Developmental Biology, 2022)
Cryptotanshinone (CT), a natural compound derived from Salvia miltiorrhiza Bunge (Danshen, a traditional Chinese medicine), has been shown antitumor activity in various cancers. However, it remains unclear whether CT has a potential therapeutic benefit against ovarian cancers. The aim of this study was to test the efficacy of CT in ovarian cancer cells in vitro and using orthotopically implanted HEY A8 human ovarian cancer cells into NSG mice in order to determine its antitumor efficacy and explore the molecular mechanism underlying CT’s antitumor effects. We found that CT inhibited the proliferation, migration, and invasion of OVCAR3 and HEY A8 cells while sensitizing the cell responses to chemotherapy drugs paclitaxel and cisplatin. CT also suppressed ovarian tumor growth and metastasis in immunocompromised mice orthotopically inoculated with HEY A8 cells. Mechanistically, CT degraded oncogene c-Myc by promoting ubiquitination and disrupting the interaction with its partner protein Max. CT also attenuated the FAK signaling and degraded FAK in both cell lines. Knockdown of c-Myc using lentiviral CRISPR/Cas9 nickase resulted in a reduction of FAK expression, which phenocopies the effects of CT and 10058-F4. Taken together, our studies demonstrate that CT inhibits primary ovarian tumor growth and metastasis by degrading c-Myc and attenuating the FAK pathway.